Media, youth, and education: modes of constructing the “other” in culture - Bueno Fischer, Rosa Maria (Education Policy Analysis Archives, 2008)
The aim of this paper is to discuss a research project conducted between 2002-2005 in Porto Alegre, Brazil. The focus was exploring how a group of 90 students perceived media?s discourse ? especially television ? about ?youth.? Through the analysis of the discourse of both media and students, the research team selected a main theme for inquiry: the construction of the ?other? in the mass media and the perception of differences among these groups in relationship to social, economic, generational, racial, ethnic, and physical appearance dynamics. This research uses Foucaltian categories of analysis, specifically the concepts of normality, abnormality, and modes of subjectivity, and Hannah Arendt conceptualization about public and private spheres ? which allows for discussion of the multiple performances and images operating through media mechanisms. This work also uses other concepts like difference and alterity, follwoing Carlos Skliar studies.